Of Revenue Without Rulers: Public Goods in the Egalitarian Cities of the Indus Civilization - Green, Adam S. (Frontiers in Political Science, 2022)
The archaeology of collective action addresses a widespread myth about the past–that premodern societies were despotic, and only produced public goods when everyday people convinced a separate and distinct ruling class to provide them. Archaeological evidence from the Indus civilization ( 2600–1900 BC), home to the first cities in South Asia, reveals that Indus cities engaged in a remarkably egalitarian form of governance to coordinate different social groups, mobilize labor, and engage in collective action, thus producing a wide range of public goods. These public goods included, but were not limited to, water infrastructure, large public buildings, and urban planning–all of which helped Indus cities invent new technologies, grow, and thrive. Many intersecting institutions contributed to Indus governance, including civic bureaucracies that gathered the revenue necessary to mobilize labor in pursuit of collective aims, as well as guild-like organizations that coordinated the activities of numerous everyday communities and ensured the equitable distribution of information within Indus cities. A wide range of large and small public buildings, information technologies, and protocols for standardized craft production and construction attest to this egalitarian governance. Through these institutions, Indus governance incorporated the “voice” of everyday people, a feature of what Blanton and colleagues have described as good governance in the past, in absence of an elite class who could be meaningfully conceptualized as rulers.